THE TARIQA SHATTARIYYA: ETNO-TARIQA AND HOMETOWN “REMINDER TOOL” OF PARIAMAN-TRANSLOCAL IN INDONESIA - Ziaulhaq Hidayat (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
This study aimed to discuss the Tariqa Shattariyya (TS) in the Pariaman-translocal community of Indonesia. TS is an integral part of the life activities associated with these community groups. This research method is qualitative and relies on in-depth observation of the object under study. The perspective used by ethnography seeks to fully describe the Pariaman people who migrate to various regions of Indonesia. This study focused on Medan and Bekasi cities to explore TS and the Pariaman-translocal community. The findings of this study explain that wherever the Pariaman people migrate to Indonesia, the Syattariyah order will constantly be revived and developed there. As an ethno-tariqa, TS was formed by introducing it to the Pariaman culture. Through ethno-tariqa, it determines the identity of the Pariaman-Translocal community in order to constantly connect in their migrations. Therefore, the mission of the Pariaman-Translocal community is to disseminate TS as a “connection tool”  overseas and form a spiritual ethnic community. TS is a “reminder tool” of their hometown used as a reference for their life overseas.